The status and impact of gas pipelines in the Caucasus region Determining energy policies - Ibrahim, Nahla Ismail (The International and Political Journal, 2025)
The routes of natural gas pipelines between different countries are an indicator of the nature of international relations between the starting and ending points, as well as the transiting parties. This pipeline embodies the balance of international relations, fluctuating between the points of cooperation and conflict, and the intermediate issues between them. For the pipeline to continue fulfilling its economic and developmental role, it requires continued political consensus, the absence or fluctuation of which could lead to a halt in the flow of natural gas. This is what we saw with the Russian-Ukrainian war, which halted the flow of Russian gas to Europe due to its military support for Ukraine. Therefore, the geopolitical importance of gas pipeline routes, coupled with the expansion of international competition, is evident. This will lead to the establishment of political and economic relations that benefit all parties in the Caucasus region